Significant Decrease in Scientific Performance after Completing Habilitation as an Academic Milestone: A Bibliometric Analysis of 742 Web of Science Profiles with Focus on Orthopedic and Trauma Surgeons - Razaeian, Sam; Hoffmann, Julia; Liodakis, Emmanouil; Örgel, Marcus (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
Habilitation is a procedure by which one of the highest university degrees is achieved in the field of medicine in Germany. We hypothesize that this academic milestone represents an incentive for scientific productivity that drops off once a scientist has reached this career steep. This study aims to compare scientific performance of German scientists before and after completing this milestone with special focus on orthopedic surgeons and traumatologists (O&T).Scientists who had completed their habilitation in human medicine were researched from public announcements in the period Jan–Dec 2018. The periods Jan 2016 to Dec 2018 and Jan 2020 to Dec 2022 were defined as pre- and post-habilitation phases, respectively. Scientific performance was calculated using normalized citation percentiles (NCPs) from author records in Web of Science. Association between sex, subject area, and change in performance were analyzed.NCP values of 742 scientists were analyzed showing a significant decrease after completing habilitation (p < 0.001). This applied to men and women (p = 0.015, p = 0.003) and non-surgical disciplines (p = 0.001), while surgical disciplines such as O&T only demonstrated a statistically non-significant decrease. Interestingly, women showed an increase in performance after habilitation in this male-dominated discipline at only 4.5% (2) females compared to males. Most scientists in the population experienced a decline in performance (53.9% [400]). This drop amounted to over 50% in 35.5% (142) of these cases. No association was found regarding gender or subject area.Scientific performance seems to be incentive-dependent and significantly decreases after completing a career milestone in Germany. This decline is not statistically significant in O&T; women, who are strongly underrepresented, even show an increase in performance.
Keywords: scientific performance; citation; normalized citation percentile; h-index; habilitation